Assessing the Efﬁciency of Jakarta Islamic Index-Linked Investing - Salahuddin, Anwar; Hermansyah, Anton (The Indonesian Capital Market Review, 2012)
The passive investing is getting easier with the fund that mimics indexes or market portfolio. The sharia market instruments is the answer to the need of Muslim investors. In the future, there are possibilities for more index-linked funds, exchange traded funds, and index-based derivatives in Indonesia including their sharia counterpart. We analyze the performance of Jakarta Islamic Index in three aspects, proﬁtability, stability, and efﬁciency, compared with ordinary indexes, the BISNIS-27 Index and the LQ45 Index. The proﬁtability is analyzed using Fama and French Three Factors model. The stability aspect is analyzed using Sharpe Return Based Style Analysis and Style Drift. The efﬁciency aspect is analyzed using the simulation of indexes with different assets allocation. The result is the JII needs to tighten the selection criteria for its constituents to be more efﬁcient than the BISNIS-27 and LQ45 indexes and it is better to add fundamental criteria to the constituent selection.